Predicting the neural effect of switching from donepezil to galantamine based on single‐photon emission computed tomography findings in patients with Alzheimer's disease. Issue 2 (26th June 2015) - Oka, Mizuki; Nakaaki, Shutaro; Negi, Atsushi; Miyata, Jun; Nakagawa, Atsuo; Hirono, Nobutsugu; Mimura, Masaru
Abstract: Background: A number of neuroimaging studies have addressed the specific effect of treatment with cholinesterase inhibitors on the frontal lobe in patients with Alzheimer's disease (AD). However, the neural effects of cholinesterase inhibitors on both apathy and executive dysfunction remain unclear. We examined whether baseline regional cerebral blood flow, as determined by using single‐photon emission computed tomography, is capable of predicting changes in apathy and executive dysfunction in response to AD patients switching from donepezil to galantamine therapy. Methods: We conducted a 24‐week, prospective, open‐label study of AD patients treated with galantamine who did not respond to previous treatment with donepezil. Single‐photon emission computed tomography was performed at baseline, and behaviour and cognitive assessments including the Mini‐Mental State Examination, the Japanese version of the Alzheimer's Disease Assessment Scale‐cognitive subscale, the Frontal Assessment Battery, the Neuropsychiatry Inventory Brief Questionnaire Form, and the Dysexecutive Questionnaire were conducted at three time points (baseline and after 12 and 24 weeks of galantamine therapy). Results: After galantamine therapy, the Neuropsychiatry Inventory Brief Questionnaire Form scores (apathy, irritability, and aberrant motor symptoms) and the Dysexecutive Questionnaire score improved significantly. The single‐photon emission computed tomography findings showed that lower baseline regional cerebral blood flow values in several frontal areas, including the dorsolateral and ventrolateral prefrontal cortex, the anterior cingulate, and the orbitofrontal cortex, predicted greater reductions in the score for apathy (distress) on the Neuropsychiatry Inventory Brief Questionnaire Form and the Dysexecutive Questionnaire score after patients switched from donepezil to galantamine therapy. Conclusions: Our study suggests that galantamine therapy, unlike donepezil, is characterized by a dual mechanism of action that may increase acetylcholine and the nicotinic receptor‐modulation effect within the frontal lobe, both of which are associated with apathy and executive dysfunction in AD patients.